Invisíveis – Índice multidimensional da pobreza rural local - Hanzen, Márcia (2023)
This thesis contributes to closing the gap when it comes to analyzing smaller populations or groups of very specific farmers that cannot be detected in large-scale statistical studies. Thus, the research question answered was: is it possible to establish a local Multidimensional Rural Poverty Index - IPMR-L for specific groups such as family farmers in the municipality of Medianeira-PR? The general objective of this research is to establish a local rural multidimensional poverty index - IPMR-L for the municipality of Medianeira. The specific objectives are: a) to describe the constitution of multidimensional poverty and its indices; b) discuss the fight against poverty in the rural world and the role of existing public policies in government spheres aimed at fighting poverty in the rural world; c) develop a multidimensional local rural poverty index - IPMR-L; d) apply the rural multidimensional poverty index – IPMR-L, in the municipality of Medianeira-PR. In the theoretical framework, multidimensional poverty and its composition were discussed, bringing Amartya Sen's thought and the theory of capabilities to the discussions. The composition presented 4 dimensions: education, with 2 indicators; health, with 2 indicators; life standard; with 7 indicators and rurality with 15 indicators. The results of the variables serve as a diagnosis for the development of public policies focused on solving the most pressing problems so that family farmers feel remembered, represented and strengthened in the production and commercialization process of what they may start to produce as a result of these policies. The IPMR-L model could be the parameter to develop powerful and more assertive public policies for the localities, as well as serve to measure the needs of the population in order to develop policies aimed at endogenous development, diagnosing local problems, correcting possible deviations from public policies and listing local resources to promote a new coherence between internal and external traditional elements, trying to harmonize ecological, socio cultural and economic conditions. The study's objectives were met and the results demonstrated that it is possible to establish a rural indicator for municipalities based on the understanding of their local specificities.